CT EVALUATION OF MEDIASTINAL MASSES: A STUDY OF 80 CASES - Ahmed, Ishtiaq; Farooq, Ahsen; Naeem, Tahir; Jaffar, Tariq; Rehman, Atiq -ur- (Journal of Ayub Medical College Abbottabad, 1996)
Eighty patients with mediastinal masses were imaged with computed tomography (CT). Results were analyzed with regard to the ability of CT to demonstrate the masses, their location, their morphology, and their encroachment upon or displacement of adjacent mediastinal structures. CT images were compared with plain chest radiographs which were available in all cases. CT depicted all lesions successfully with good anatomic detail. Among the 80patients the largest number of cases (n =51) were found to be having lymphadenopathy with Hodgkin's lymphoma in 57% and non-Hodgkin's lymphoma in J5% of cases. CT is regarded as the best single radiological investigation for evaluating a mediastinal abnormality demonstrated on a high-kV chest radiograph or for detecting occult mediastinal disease.